STRATEGI KOMUNIKASI PEMASARAN DALAM MENINGKATKAN MINAT BERKUNJUNG DI MUSEUM NEGERI PROVINSI SUMATERA UTARA - Hulman Sinurat; Irene Silvia; Sabrin Sabrin (Lembaga Penenlitian dan Pengabdian kepada Masyarakat Universitas Darma Agung, 2020)
This study aims at finding the marketing communication strategy at the State Museum of North Sumatra Province, interest in visiting the North Sumatra Province State Museum, the barriers to marketing communication strategies in increasing interest in visiting the North Sumatra Province Museum. The research method is a descriptive study with a qualitative approach. The phenomenon that occurs in the Museum of the Province of North Sumatra is the lack of budget disbursed by the Government of North Sumatra Province in which the total budget is seniliai 1.5 billion and these funds are purely funds originating from the APBD and the funds are not entirely intended for marketing the museum but overall museum needs. The lack of facilities makes the museum think about how to increase the interest of visitors in every day, besides, the low variety of cultural activities in which the museum is the sole manager, cultural activities are a staple product for every visitor.